Risk-Based inspection for ammonia storage unit by using PRIMS: A case study - Marzuki, Omar; Azizan, Ramli; Kharul Anwar, Johari; Saeid, Mohammed Faraj (Institution of Engineering and Technology, 2022)
Risk-based inspection (RBI) is a method that applies risk analysis as its foundation. In this study, RBI methodology is applied on an ammonia storage unit in a specialized bioprocess facility. A liquid ammonia is stored in two pressure vessels. This study aims to determine the level of risk posed by the storage unit and decide the right inspection method and timeframe to conduct the inspection on the unit. The methodology used is based on PRIMS-RBI software with reference to American Petroleum Institute, API 581 Risk-based inspection methodology. This study is the first application of RBI for ammonia storage tank in bio-processing facilities in Malaysia. Based on the analysis performed, the most credible damage mechanism experienced by the unit is identified as internal and external wall thinning. Also, based on the analysis, the probability of failure of this unit is identified as “Low”, and the consequences of failure is identified as “Catastrophic”. Based on the risk analysis, the risk level of this unit is categorised as “Medium-High” level. This “medium-high risk” is caused by the property of the fluid stored in this device, which is toxic in nature and may potentially cause serious safety and health impact to the surrounding population.